Case Report: Clinical benefit from multi-target tyrosine kinase inhibitor and PARP inhibitor in a patient with cancer of unknown primary with BRCA1 large genomic rearrangement - Yu, Ling; Lin, Jietao; Li, Hanhan; Sun, Lingling; Wang, Shubo; Chen, Yaoxu; Chen, Hanrui; Lin, Lizhu (Frontiers in Pharmacology, 2023)
Background: Cancer of unknown primary (CUP), which accounts for 3%–5% of new cancer cases every year, involves the presence of a type of histologically confirmed metastatic tumors whose primary site cannot be confirmed by conventional diagnostic methods. This difficulty in identifying the primary site means that CUP patients fail to receive precisely targeted therapy. Most patients are treated with empiric chemotherapy, with a median survival of 6 months and even poorer prognosis within an unfavorable subset of CUP. Case report: An 80-year-old woman presented with masses in the abdomen. Following comprehensive imagological and immunohistochemical examinations, she was diagnosed with CUP. She emphatically declined chemotherapy; thus, anlotinib has been administered with patient consent since 02/07/2019, and stable disease (SD) was observed for 2 years. During subsequent treatment, a large genomic rearrangement in BRCA1 was identified in the patient via NGS, and SD was observed for a further 6 months following olaparib treatment. The type of LGR identified in this patient was discovered to be BRCA1 exon 17-18 inversion (inv), which has never been previously reported. Conclusion: For CUP patients, a chemo-free regimen seems to be acceptable as a first-line treatment, and NGS-guided targeted treatment could improve patient outcomes.